Comparative effectiveness of anti-fibrosis treatment in patients after HCV infection and in patients with non-alcoholic fatty liver disease (NAFLD) - Nadiia Gavryliuk; Ihor Hospodarskyy; Oksana Prokopchuk; Olha Krekhovska-Lepiavko; Borys Lokay; Mykhailo Havrylyuk (Kazimierz Wielki University, 2021)
Due to the high prevalence of NAFLD and CHC, these two pathologies will progress and contribute to the progression of fibrosis. Unfortunately, nowadays there is no single treatment strategy for such patients. That is why, in most cases a variety of treatment regimens on the base of different hepatoprotectors are prescribed. Instead, there is evidence that the use of some hepatoprotectors has no influence on fibrotic processes in the liver or can even exacerbate them. In order to study the antifibrotic effect of hepatoprotectors in patients with posthepatic fibrosis after HCV infection and in patients with NAFLD, we studied the results of prescribing the hepatoprotective drug bicyclol.